2013
DOI: 10.1016/j.bbr.2012.10.046
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sodium butyrate on methamphetamine-sensitized locomotor activity

Abstract: Neuroadaptations associated with behavioral sensitization induced by repeated exposure to methamphetamine (MA) appear to be involved in compulsive drug pursuit and use. Increased histone acetylation, an epigenetic effect resulting in altered gene expression, may promote sensitized responses to psychostimulants. The role of histone acetylation in the expression and acquisition of MA-induced locomotor sensitization was examined by measuring the effect of histone deacetylase inhibition by sodium butyrate (NaB). F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 43 publications
1
15
0
Order By: Relevance
“…Moreover, METH upregulated Egr2 and c‐fos expression via increased H4K5Ac binding at the promoters of these genes . In a subsequent article, Harkness et al . also reported that acute METH increased H4 acetylation in the striatum.…”
Section: Role Of Epigenetics In Psychostimulant Exposurementioning
confidence: 90%
See 1 more Smart Citation
“…Moreover, METH upregulated Egr2 and c‐fos expression via increased H4K5Ac binding at the promoters of these genes . In a subsequent article, Harkness et al . also reported that acute METH increased H4 acetylation in the striatum.…”
Section: Role Of Epigenetics In Psychostimulant Exposurementioning
confidence: 90%
“…Moreover, METH upregulated Egr2 and c-fos expression via increased H4K5Ac binding at the promoters of these genes. 62 In a subsequent article, Harkness et al 63 also reported that acute METH increased H4 acetylation in the striatum. It is thus possible that METH-induced increased H4 acetylation may be secondary to increased CBP expression because increased CBP expression is associated with increased histone acetylation.…”
Section: Self-administration (3-4 Weeks; 4-h Session)mentioning
confidence: 94%
“…Knockout of HDAC5 promoted the hypersensitive responses, which was completely reversed by re-expression of HDAC5 in NAc [7]. Our present study further suggested the special role of HDAC5 in METH-induced behavioral sensitization.Administration of HDAC inhibitors (HDACis) increased histone acetylation in the central nervous system and was supposed to modulate drug addiction [8,9]. However, different HDACis were reported to have different, even opposite effects on drug addiction.…”
mentioning
confidence: 99%
“…Administration of HDAC inhibitors (HDACis) increased histone acetylation in the central nervous system and was supposed to modulate drug addiction [8,9]. However, different HDACis were reported to have different, even opposite effects on drug addiction.…”
mentioning
confidence: 99%
See 1 more Smart Citation